Does monetary policy reinforce the effects of macroprudential policy - Adam Geršl; Barbara Livorová (Charles University in Prague, Institute of Economic Studies (IES), 2023)
This paper contributes to studying the interaction between monetary and macroprudential policies by examining whether the impact of macroprudential policy on credit and house price growth differs between the two key phases of monetary policy cycle, i.e. monetary policy tightening and loosening. The dataset covers 33 advanced and 33 emerging market countries in the period 1990 - 2019 in quarterly frequency. Using the GMM estimation method, the results show that tightening of monetary policy does on average reinforce the effects of macroprudential policy on credit and house prices. Furthermore, we show that this reinforcing effect works for some but not all types of macroprudential policy measures, and that the results differ between advanced countries and emerging markets.
Keywords: E52; E58; G21; G28; E32; 330; Macroprudential Policy; Monetary Policy Cycle; Credit Growth; House Price Growth; Interaction of Policies